Alternative Formula for Rigid Pavement Stress Calculation in Corner Load Conditions - Saverio Olita; Maurizio Diomedi; Donato Ciampa (The Baltic Journal of Road and Bridge Engineering)
The design of rigid pavements is historically based on the classical Theory of proposed by Westergaard in 1929, which considers the rigid pavement as a thin plate resting on an elastic ground with a Winkler reaction, imposing the congruence of vertical displacements at the points of contact between the pavement structure and the ground. Westergaard’s Theory provides expressions for the calculation of maximum stress in concrete slabs for interior, edge and corner load conditions. This work focuses on the development of a Finite Element model, implemented in the ANSYS® environment and calibrated on the basis of the results of the in-scale experimental model developed by Lall and Lees in 1983. The implementation of the FE model was performed through a set of steps capable of reproducing physical and mechanical conditions of the true model, which was further intended to be used for numerical analysis. After the FE model was developed, it was possible to carry out multiple simulations pursuing three main aims: to evaluate the effect of the variation of material properties on the slab stress state, to compare the maximum stresses for the interior and edge load conditions considering Westergaard’s Theory, the experimental data and the results of the numerical model, and to use the developed and calibrated model to formulate an alternative mathematical expression, which would allow calculating the stress in corner load conditions.